E-Zakat in the digital era: A study on the determinants of usage intention based on UTAUT and TAM - Ariyani, Diyah; Kurniawan, Heri; Nurhadi, Bayu (Indonesian Journal of Islamic Economics Research, 2024)
This study aims to analyze the factors that influence the intention to use the E-Zakat service with the UTAUT (Unified Theory of Acceptance and Use of Technology) and TAM (Technology Acceptance Model) approach. This research also analyzes the acceptance and use of technology towards an individual’s interest in using the E-Zakat service. This study uses a quantitative method with the SmartPLS version 3 analysis tool. The data used is primary data by distributing questionnaires to 100 sample respondents. The results showed that there is a significant influence between the acceptance and use of technology on an individual’s interest in using the E-Zakat service.